Marx's temporalities - Tomba, Massimiliano, 1968- (Historical materialism book series ;, 2013)
The book rethinks key categories of Marx's work beyond any philosophy of history, showing how the plurality of temporal layers that are combined and come into conflict in the violently unifying historical dimension of modernity are central to Marx's thought.